Bridge: Person‐Centered Collaborative Care for Patients with Serious Mental Illness and Cancer. (29th January 2019) - Irwin, Kelly E.; Park, Elyse R.; Fields, Lauren E.; Corveleyn, Amy E.; Greer, Joseph A.; Perez, Giselle K.; Callaway, Catherine A.; Jacobs, Jamie M.; Nierenberg, Andrew A.; Temel, Jennifer S.; Ryan, David P.; Pirl, William F.
Abstract: Background: Individuals with serious mental illness (SMI) experience increased cancer mortality due to inequities in cancer treatment. Psychiatric care at cancer diagnosis may improve care delivery, yet models for integrating psychiatry and cancer care are lacking. We assessed the feasibility and acceptability of a person‐centered collaborative care trial for SMI and cancer. Subjects, Materials, and Methods: We developed the Bridge intervention for patients with SMI (schizophrenia, bipolar disorder, and severe major depression) and cancer. Bridge includes proactive identification of SMI, person‐centered care from a psychiatrist and case manager, and collaboration with oncology. We conducted a 12‐week, single‐group trial in patients with SMI and a new breast, gastrointestinal, lung, or head/neck cancer. We assessed the feasibility of patient identification, enrollment and study completion; evaluated acceptability and perceived benefit with exit interviews with patients, caregivers, and oncology clinicians; and examined change in psychiatric symptoms with the Brief Psychiatric Rating Scale (BPRS). Results: From November 2015 to April 2016, 30/33 eligible patients (90.9%) enrolled, and 25/29 (86.2%) completed assessments at all timepoints, meeting feasibility criteria. Of 24 patients, 23 (95.8%) found meeting with the psychiatrist helpful; 16/19 caregivers (84.2%) shared that Bridge addressed key caregiving challenges. Oncology clinicians evaluated Bridge as "very" or "most" useful for 94.3% of patients. Exit interviews with all participant groups suggested that Bridge fostered patient‐clinician trust, increased access to psychiatric treatment, and enabled patients to initiate and complete cancer treatment. Psychiatric symptoms on the BPRS improved from baseline to 12 weeks. Conclusion: Bridge is a feasible and acceptable care delivery model for patients with SMI, their caregivers, and oncology clinicians. Randomized trials are warranted to assess the efficacy of improving cancer outcomes in this underserved population. Abstract : New models of care delivery that promote collaboration between oncology and mental health are urgently needed. The Bridge intervention, a person‐centered model of early, integrated psychiatric and cancer care for patients with serious mental illness, was developed to improve cancer outcomes in this underserved population.